2011
DOI: 10.2202/1548-923x.2250
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Nursing Practice Education: Preparing the Next Generation

Abstract: Undergraduate nursing practice rotations today are quite different from what many practicing nurses experienced during their own education. This is especially true of community health practice rotations. Increasingly, non-traditional community health sites are being used as practice sites-sites such as schools, homeless shelters, non-profit agencies, and even churches. Increasingly, non-traditional practice experiences are eclipsing traditional practice experiences involving home care and public health. Why ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…It is our responsibility to take the economic and nursing shortage issues our country is currently facing into consideration when trying to solve problems for creative clinical experiences [15] . As we work to this end, we must encourage students of nursing to become agents of change while learning to collaborate and incorporating health promotion, illness prevention and primary health care to individuals residing in their chosen communities.…”
Section: Resultsmentioning
confidence: 99%
“…It is our responsibility to take the economic and nursing shortage issues our country is currently facing into consideration when trying to solve problems for creative clinical experiences [15] . As we work to this end, we must encourage students of nursing to become agents of change while learning to collaborate and incorporating health promotion, illness prevention and primary health care to individuals residing in their chosen communities.…”
Section: Resultsmentioning
confidence: 99%
“…Many nursing programs have turned to non‐traditional clinical settings as opportunities for clinical placement in traditional public health clinical sites have continued to shrink. Other authors have identified the need to provide enhanced student support and public health role modeling as well as improved faculty development opportunities in public health to ensure students have optimal clinical experiences in non‐traditional clinical settings (Joyce et al, ; Leurer et al, ; Pijl‐Zieber, Barton, Awosoga, & Konkin, ; Pijl‐Zieber & Kalischuk, ; Wade & Hayes, ). It is imperative to continue to work with our traditional clinical settings in county and governmental public health agencies to provide clinical placements to as many students as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The survey reported that Canadian nurse educators rely upon student placements such as correctional facilities, Aboriginal communities, international placements, rural and parish settings; reports that are corroborated in other regions (Sloan, Keely, & Groves, 2008;Stewart, 2007). Student learning in these community-based settings has been described as transformative, with students gaining enhanced critical thinking competencies (Pijl-Zieber & Kalischuk, 2011;ReimerKirkham et al, 2005;Reimer-Kirkham, Van Hofwegen, & Pankratz, 2009). Despite this widespread reliance on alternative placements and the reports of transformative learning, few studies have reported the host agency perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits to students included the development of skills in communication, critical thinking, and collaboration. Students are also reported as gaining a community perspective and commitment to health promotion in the community, and an awareness of diversity and cultural dynamics (Keller et al, 2011;Pijl-Zieber & Kalischuk, 2011). Plowfield, Wheeler, and Raymond (2005) and Leurer et al (2011) described benefits for students that included the opportunity to identify new health care needs, attend to more complex client needs, and opportunities to practice broader health promotion strategies.…”
Section: Introductionmentioning
confidence: 99%